2021
DOI: 10.1186/s12882-021-02292-3
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis patients perceived exercise benefits and barriers: the association with health-related quality of life

Abstract: Background Patients on hemodialysis have less exercise capacity and lower health-related quality of life than healthy individuals without chronic kidney disease (CKD). One of the factors that may influence exercise behavior among these patients is their perception of exercise benefits and barriers. The present study aimed to assess the perception of hemodialysis patients about exercise benefits and barriers and its association with patients’ health-related quality of life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…Psychologically, exercise can improve depression of patients (Afsar et al, 2018) and improve QOL (Cho et al, 2018). Therefore, exercise being considered beneficial as a facilitator to exercise, which is similar to the result of a quantitative study (Ghafourifard et al, 2021). Other study suggests that motivation for exercise may stem from awareness of the benefits of exercise (Clarke et al,2015).…”
Section: Discussionsupporting
confidence: 74%
“…Psychologically, exercise can improve depression of patients (Afsar et al, 2018) and improve QOL (Cho et al, 2018). Therefore, exercise being considered beneficial as a facilitator to exercise, which is similar to the result of a quantitative study (Ghafourifard et al, 2021). Other study suggests that motivation for exercise may stem from awareness of the benefits of exercise (Clarke et al,2015).…”
Section: Discussionsupporting
confidence: 74%
“…Studies of patients’ opinions and experiences with IE show that they view it positively, particularly when interventions include personal instruction and follow-up [ 27 , 28 , 29 , 30 ]. However, patients also perceive barriers that include exercise equipment [ 31 ], safety concerns [ 16 , 29 , 30 ], disease distress [ 30 ], and nursing workloads [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of patients’ opinions and experiences with IE show that they view it positively, particularly when interventions include personal instruction and follow-up [ 27 , 28 , 29 , 30 ]. However, patients also perceive barriers that include exercise equipment [ 31 ], safety concerns [ 16 , 29 , 30 ], disease distress [ 30 ], and nursing workloads [ 31 , 32 , 33 ]. Studies have found that nurses’ attitudes towards patients’ physical activity are correlated with patients’ activity levels, i.e., patients are less physically active when their nurses believe that physical activity is unimportant, or lack the time or feel unqualified, to discuss physical activity with patients [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CKD benefit greatly from exercise training, which includes both aerobic and resistance activities, as well as increased muscle strength and lower blood pressure (BP) [26]. PE also benefits dialysis patients' physical health by improving CV function, blood pressure, muscle strength, and nutritional status, as well as improving dialysis quality [28]. For HD patients, PA in everyday life has a greater impact on QoL than it does in the general population [29].…”
Section: General Impactmentioning
confidence: 99%